Информационная технология и метод управления ресурсами информационной системы в сети с использованием концепции политик - Саенко, В. И.; Голубев, А. С. (My University, 2008)
У статті описаний метод керування ресурсами інформаційної системи в мережі, заснований на використанні концепції політик при ухваленні рішення про зміну стану об'єкта. Запропоноване використання спеціальних логічних конструкцій, сумісних з єдиною технологією менеджменту в комп'ютерних мережах. Правильність отриманих рішень підтверджується на прикладах. The article describes information technology and a method of managing the resources of an information system in a network, based on the use of the concept of policies when deciding to change the state of an object. The network is considered as a dynamic system, the main functional objects of which are resources. The use of special logical constructions compatible with uniform management technology in computer networks is proposed. The correctness of the solutions obtained is confirmed by examples.
Keywords: компьютерная сеть; информационная технология; информационная система; QoS; качество обслуживания; управление с помощью политик; показатель качества